SKILLS DEVELOPMENT TRAINING OF CHEMICAL ENGINEER UNMSM AND NEEDS OF LABOUR MARKET DEMAND - García P., José (2008)
The Universities that form human resources, they should be updated with respect to the demands of the labor market and labor skills that are required. In this work, you try to explain the importance of feedback on what the job market requires some of the organizations that are chemical engineers, so has been evaluated labor market information 2007 and 2008.